HUBUNGAN MOTIVASI EKSTRINSIK KINERJA PETUGAS KESEHATAN TERHADAP KETIDAK LENGKAPAN PENGISIAN BERKAS REKAM MEDIS RAWAT JALAN DI RSUD PETALA BUMI PROVINSI RIAU TAHUN 2018 - Trisna, Wen Via (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
Factors that affect the achievement of one of them is the work motivation. Extrinsicmotivation is an encouragement that makes a person more enthusiastic in completing ajob. RSUD Petala Bumi still has a high percentage of incompleteness, this is due to the lowperformance of medical record officers and health workers who are suspected as a resultof low motivation of work. The purpose of this research is to know the correlation betweenrelationship of extrinsic motivation of health officer performance to incomplete filling ofoutpatient medical record file at rsud petala bumi riau province. This research method isQuantitative research, with sample of research consist of 34 people. Instrument ofresearch by using questioner. Data processing techniques used are statistical techniques,data analysis ie univariate and bivariate analysis. The result of research for workperformance relation on performance there are 16 respondents (84,2%). Relation ofcompensation to health officer performance, Compensation is not good there are 16respondents (80,0%). The relationship of supervision to the performance of healthpersonnel. of respondents who supervise is not good there are 17 respondents (77,3%)with performance of health officer is not good. Conclusion of research, There is relation ofwork performance to health officer performance in RSUD Petala Bumi Riau Province.There is a compensation relationship to the performance of health workers in RSUDPetala Bumi Riau Province. There is a supervisory relationship to the performance ofhealth workers in RSUD Petala Bumi Riau Province.Keyword : extrinsic motivation, performance, incomplete filling out of file medicalrecord